Strategi Pendidikan Politik KPU dalam Meningkatkan Partisipasi Pemilih Pemula pada Pemilihan Bupati dan Wakil Bupati Solok Tahun 2020 di Kabupaten Solok - sismita, mega (UIN Mahmud Yunus Batusangkar, 2023)
The background of this research was triggered by the urgent need to increase the political participation of novice voters in general elections in Solok Regency. Data from the Solok Regency KPU illustrates a worrying trend, with the number of first-time voters declining from year to year, as well as the presence of apathy in the political process. Therefore, this study aims to analyze the factors that influence the political participation of novice voters, formulate a political education strategy that can increase the political literacy and involvement of novice voters, and identify the obstacles that may be faced in the implementation of socialization. The research method applied in this study is qualitative research, which aims to describe the object of the phenomenon or social setting in the form of narratives and words, focusing on the KPU's political education strategy in increasing the political participation of novice voters in the 2020 Solok Regent and Deputy Regent elections. The political education strategy implemented by the Solok Regency General Election Commission in the 2020 Regent and Deputy Regent elections is seen through three strategy indicators. Thus, the political education strategy of the Solok Regency KPU focuses on face-to-face approaches, synergy with mass media, and improving the quality of volunteers to increase the political participation of novice voters in the 2020 Regent and Deputy Regent elections.